Analisis Semiotika: Makna Denotatif dan Konotatif dalam Film Spongebob Squarepants Episode 9 “Uh, Bulu Babi” Season 9 (Dubbing Bahasa Arab) - Muhammad Yazid Yaskur (Diwan: Jurnal Bahasa dan Sastra Arab, 2024)
This research aims to analyze the semiotic meaning of denotative and connotative in the use of Arabic in the episode "Uh, Bulu Babi" from the animated series SpongeBob SquarePants. The research method used is qualitative using Roland Barthes' semiotic theory, namely "Two Order Signification" with the data collection process looking for SpongeBob videos on Netflix and YouTube that use Arabic dubbing. Data was collected using observation and note-taking data collection techniques. The results of the research show that the use of Arabic provides denotative meaning, while also generating connotative meaning based on context through semiotic analysis which is reflected in the facial expressions and intonation of the characters. This illustrates the flexibility of the meaning of Arabic as reflected in the film, as well as its use that we can find in everyday life.